Boundary Fractal Analysis of Two Cube-oriented Grains in Partly Recrystallized Copper. Issue 1 (April 2015) - Sun, J; Zhang, Y B; Dahl, A B; Conradsen, K; Jensen, D Juul
Abstract: The protrusions and retrusions observed on the recrystallizing boundaries affect the migration kinetics during recrystallization. Characterization of the boundary roughness is necessary in order to evaluate their effects. This roughness has a structure that can be characterized by fractal analysis, and in this study the so-called "Minkowski sausage" method is adopted. Hereby, two cube-oriented grains in partly recrystallized microstructures are analyzed and quantitative information regarding the dimensions of protrusions/retrusions is obtained.